Effective utilization of refractory dissolved organic matters in domestic sewage allows to enhanced nitrogen removal by integrated fermentation, nitrification, denitratation and anammox process. (June 2022) - Wu, Yiling; Zhang, Xingxing; Chen, Junjiang; Wang, Chaochao; Zhang, Xiaonong; Chen, Jiaqiao; Cai, Tianning; Liu, Wenru; Li, Xiang; Wu, Peng
Graphical abstract: Highlights: Novel and robust IFNDA obtained high TN removal of 94.1% from domestic sewage. Anammox dominated TN removal in IFNDA process with the percentage of 88.6%. High ratio of acetate (54.0%) and VFAs/COD (64.5%) facilitated NO3 – -N reduction. Fermentation microbes and nitrogen conversion bacteria were isolatedly enriched. Energy-efficient IFNDA has a promising opportunity for upgrading WWTPs. Abstract: To take full advantage of refractory dissolved organic matters (rDOMs) and generate sufficient nitrate for domestic sewage treatment, this study presented a novel integrated fermentation, nitrification, denitratation and anammox (IFNDA) process in a combined ABR-CSTR reactor. The results showed that an advanced total nitrogen (TN) removal efficiency of 94.1% was obtained after over 190 days operation, resulting in effluent TN concentration as low as 3.6 mg/L. The system nitrogen removal was dominated by anammox with a high proportion of 88.6%. The high conversion rate of acetic acid (54.0%) and volatile fatty acids (64.5%) from rDOMs in domestic sewage by in-situ fermentation drove efficient denitratation. Microflora analysis indicated that the enriched Commamonas (3.5%) and Longilinea (3.3%) dominated hydrolysis and acidogenesis of organics, and Methanosaeta (9.0%) obligated acetoclastic methanogenesis in two-stage fermentation process. Thauera (8.4%) and Candidatus Brocadia (2.5%) were the core bacteria for nitrogen metabolism in the IFNDA system.